(untitled) (diségno, 2025)
To present Valeria Menchetelli’s volume, it is worth starting from here and from what the author herself suggests in her interpretation of the semantic ambiguity of this binomial, evoking the idea of “a snapshot, of an overall view taken from a particular framing, the one given by observing from a specific point of view”. [read more]